PSYCHOSOCIAL FACTORS IN THE PHARMACEUTICAL CARE OF PEOPLE WITH EPILEPSY AT COLOMBIA - VARGAS, Claudia M.; VACCA, Claudia P.; SIMBAQUEBA, Juan B (Vitae, 2013)
Background: It has been suggested elsewhere that psychosocial factors could have a negative impact on the outcomes of pharmacotherapy of patients with epilepsy. The inclusion of relevant psychosocial factors in Colombiaís context in the pharmaceutical careís methodology would optimize the detection of drug related problems and its solution by the pharmacists, thus improving pharmacotherapy outcomes. Objectives: To explore psychosocial and cultural factors that could be incorporated in the pharmaceutical care of people with epilepsy, and design a survey in order to do so. Methods: The psychosocial factors to be included were first identified using the Delphi method, and were later incorporated in the Colombia-adjusted Daderís pharmaceutical care methodology through a knowledge, attitudes and practices survey. Pilot test was carried out with 21 patients and then the survey was adjusted as necessary. The adjusted survey was applied to 70 epilepsy patients being treated in a specialized institution at Cartagena (Colombia), aged between 15 and 60 years, with at least one month of pharmacological treatment, and without a history of previous epilepsy related surgery. Univariate statistical analysis and Multiple Correspondence Analysis was applied. Results: In the pilot analysis, recurrent needs of knowledge about epilepsy and anticonvulsant treatment were found, and brochures were designed to support educational interventions. The patient's knowledge level about epilepsy and its treatment was acceptable. Correlation between subsidized health insurance and drugs access problems, along with a possible correspondence between stigma feelings and high frequency crisis were found. Conclusions: The survey allowed to explore psychosocial and cultural factors in the framework of pharmaceutical care of people with epilepsy, the detection of drug related problems and to intervene to solve them. These findings are a first approach to the description of psychosocial factors affecting the performance of pharmacological therapy, especially the dynamic of social networks, emotional problems, the maximum educational level and knowledge about epilepsy.